Home again - George, K. (Kallie), 1983- (George, K. (Kallie), 1983- Heartwood Hotel, 2018)
"Summer has come to Fernwood Forest, and the staff of the Heartwood Hotel must trust each other as they contend with their biggest challenge yet"--